Activity Of Piperacillin/Tazobactam And Cefoperazone/Sulbactam Against Pathogenic Isolates Of Enterobacteriaceae - Qamar un nisa Naz; Faisal Iqbal Afridi; Humera Rashid (ziauddin University, 2024)
Background: Enterobacteriaceae are a large family of gram negative bacteria including many genera. The emergence and spread of resistance in Enterobacteriaceae is increasing due to the production of extended spectrum beta lactamase (ESBL) enzymes. Combinations of Beta-lactam/Beta-lactamase inhibitors such as Piperacillin/Tazobactam and Cefoperazone/Sulbactam have good activity against these isolates. The purpose of this study is to determine the antimicrobial susceptibility pattern of Piperacillin/Tazobactam and Cefoperazone/Sulbactam against isolates of Enterobacteriaceae from a tertiary care hospital laboratory of Pakistan. This study validates better options for empirical antimicrobial treatment for this group of difficult to treat pathogens. Methods: A total of 2111 clinical samples were received for culture and sensitivity from both in and outpatients. Samples were inoculated on Chocolate agar, Sheep blood agar and MacConkey's agar and were incubated for 24 to 48 hours according to standard technique. All isolates belonging to the family Enterobacteriaceae identified by conventional biochemical tests were included in the study. Antimicrobial sensitivities of Enterobacteriaceae were tested and interpreted by Kirby-Bauer disc diffusion method according to Clinical Laboratory Standard Institution criteria. Results: Out of 2111 clinical samples, 214 isolates of Enterobacteriaceae were identified. Escherichia coli was recognized as the predominant pathogen (130/214; 60.75%). Frequency of extended spectrum beta lactamases producing Enterobacteriaceaewas100/214(47%) in 214 samples. Antimicrobial sensitivity was 80% (172/214) to Piperacillin/Tazobactam and 83% (178/214) to Cefoperazone/Sulbactam against the total 214 isolates of Enterobacteriaceae. Conclusion: Piperacillin/Tazobactam and Cefoperazone/Sulbactam are potential and better empirical treatment options for treating isolates of Enterobacteriaceae. This will help in reducing selection pressure on last resort antimicrobials and hence curtail antimicrobial resistance. Key Words: Antimicrobial susceptibility. Piperacillin/Tazobactam. Cefoperazone/Sulbactam. Enterobacteriaceae. Beta lactamases.